2012
DOI: 10.1159/000345645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Therapeutic Benefit of Delayed Administration of Erythropoietin following Early Hypoxic-Ischemic Injury in Rodents

Abstract: Hypoxia-ischemia (HI) and associated brain injuries are seen in premature as well as term infants with birth complications. The resulting impairments involve deficits in many cognitive domains, including language development. Poor rapid auditory processing is hypothesized to be one possible underlying factor leading to subsequent language delays. Mild hypothermia treatment for HI injuries in term infants is widely used as an intervention but can be costly and time consuming. Data suggest that the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 58 publications
5
21
0
Order By: Relevance
“…Specifically, McClure et al (McClure, et al, 2007) showed that P7 neonatal HI rats, but not HI animals treated with erythropoietin (Epo), were impaired in both spatial and non-spatial learning as compared to sham treated control counterparts, when tested as adults (P60+). Similarly, others have observed deficits in neonatal HI injured animals on spatial and non-spatial water maze paradigms (similar to those used in the present studies; (Alexander, et al, 2012, Hill, et al, 2011)). However, these studies assessed performance only in adult subjects (P83+), which resulted in residual questions regarding the influence of age at assessment on task performance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, McClure et al (McClure, et al, 2007) showed that P7 neonatal HI rats, but not HI animals treated with erythropoietin (Epo), were impaired in both spatial and non-spatial learning as compared to sham treated control counterparts, when tested as adults (P60+). Similarly, others have observed deficits in neonatal HI injured animals on spatial and non-spatial water maze paradigms (similar to those used in the present studies; (Alexander, et al, 2012, Hill, et al, 2011)). However, these studies assessed performance only in adult subjects (P83+), which resulted in residual questions regarding the influence of age at assessment on task performance.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies from our group and others have assessed both spatial and non-spatial learning across multiple models of developmental brain injury, including models of neocortical microgyria and neonatal hypoxia-ischemia (Alexander, et al, 2012, Hill, et al, 2011, Hyde, et al, 2002, McClure, et al, 2007, Threlkeld, et al, 2012). Specifically, McClure et al (McClure, et al, 2007) showed that P7 neonatal HI rats, but not HI animals treated with erythropoietin (Epo), were impaired in both spatial and non-spatial learning as compared to sham treated control counterparts, when tested as adults (P60+).…”
Section: Discussionmentioning
confidence: 99%
“…5 Critically, repeated injection with 5000 IU/kg rEpo daily for three days, started immediately after HI, was more neuroprotective after seven days recovery, than either a single dose of 5000 IU/kg or three injections of 30,000 IU/kg, 9 but neuroprotection was largely lost when treatment was delayed for 1 to 3 h after HI. 10 This finding parallels the experience with mild induced hypothermia that optimal neuroprotection after acute HI injury is seen when cooling is started within the first 6 h and continued until secondary events such as seizures have resolved, after approximately three days. 11 This suggests that continued exposure to rEpo during this critical phase will be needed for optimal outcomes after acute HI.…”
Section: Introductionsupporting
confidence: 71%
“…Although physical cooling had been used in pre-clinical and clinical practice, challenges hinder clinical feasibilities may include disruptions of coagulation system (Mohr, et al, 2013), cardiac function (Egginton, et al, 2013), and fluid pH (Groger, et al, 2013). Moreover, conventional methods in physical cooling processes are costly and time-consuming (Alexander, et al, 2012). We show in previous and current investigations that our NTR compounds effectively reduce the brain temperature and do not show the adverse effects seen with physical cooling (Choi, et al, 2012, Lee, et al, 2014, Wei, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%